Endodontic implications and innovative preventive strategies during novel COVID-19 pandemic requiring emergency endodontic treatment - Navin Mishra; Isha Narang; Ragini Mishra; Krishna Biswas; Dristi Kaushal; Priyankar Singh; AK Sharma (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Endodontics a specialty branch in dentistry frequently deals with endodontic emergencies and during this COVID-19 pandemic Emergency Root Canal Treatement (ERCT) is often required to manage acute pulpitis with or without space infections. There are various routes of disease transmission in endodontics. When treating patients requiring emergency access opening the treating doctor should be extremely vigilant and cautious regarding its spread and containment of COVID-19 virus by utilizing certain innovative strategies such as HEPA filters, High volume extraoral suction, and other devices manufactured from Polyethlene to safeguard from aerosols generated during emergency endodontic therapy.